Art in Tanzania 1999. - Goscinny, Yves; National Museum Dar es Salaam; East African Movies, Dar es Salaam (Dar-es-Salaam : East African Movies Ltd., 1999)
Amonde, Omary ; Bogaert, Pascal ; Boute, Doula ; Chikoko, David ; Costales, Miguel ; Dastani, Simuni ; Hamedi, Abdul ; Hamedi, Athumani ; Hammersley, Oenone ; Jengo, Elias ; Kilaka, John ; Laurent, Véronique ; Lilanga, George ; Ludovick, Florian ; Lutashobya, Emmanuel ; Makuti, Antoni Chipanda ; Malayo, Kashmiri ; Malikita, Maurus Michael ; Mandawa, Doreen ; Mawji-Patel, Ayesha ; Mayige, Petro Paulo ; Merve, Dalene Van der ; Mikidadi, Bush ; Mkura, Abdul Amonde ; de Moor, Marianne ; Mpuika, Joakim Adriano ; Msagula, Damian ; Msole, Helman Kidswanta ; Pandu, Ibrahim A.H. ; Raza, Mohamed ; Saidi Chilamboni, Abdallah ; Scheuning, Jackie ; Sey, Rashidi Husseini ; Sõrnãs, Clara ; Sulemanji, Muzu ; Sutila, Petra ; Y.G. ; Yengi, Poni
Engels
Art in Tanzania 1999, National Museum Dar-es-Salaam / East African Movies Dar-es-Salaam, 11 - 12.1999
boek